GÊNERO, RAÇA, DISCRIMINAÇÃO: O TOM DA COR NA DIREÇÃO DA ESCOLA PÚBLICA. - Brunelli, Conceição Aparecida Garcia (2007)
The objective of this work was to investigate the afro-descendant principal women s careers in the public education system and the process of build their own social identity, cultural of gender and race. In fact, the afro-descendant women researched built their identities into dangerous and deep waters: Gender relationships and racial relationships. The research allowed us to discover the selective process that these women whom trespassed the double-barrier of the relationships of gender and race and achieved a professional position of public school principals in their careers. The main question that we followed in this research, shows the paths of life of afro-descendants women who chose the teacher s career, the difficulties found during their personal path, academic and professional paths, their experiences, frustrations, expectations, prejudices and discriminations found along the way until achieve the position in their public career, their social rise, their start in this career and the power relationships beyond gender and race questions. The research still approach on how these difficulties influences over the building process of these women s identities, and their relationships between their colleagues, white men and white women. These empiricists informations were collected over informal conversations and based on these women s memories, written depositions and semi-structured interviews. All collected depositions allowed us to join informations who were interpreted using Foucault s Theory of Power and let us to comprehend and reflect about the individual and collective identities' building process.